José Ortega y Gasset y los principios de la psicología científica en España - "escorzo" - Horváth, Petra (Acta Hispanica, 2009)
My essay discusses the rise of scientific psychology in Spain and the role José Ortega y Gasset played in its formation. From the second half of the 19th century, as part of the effort to catch up with the scientific development that took place in Europe, Spain turned with great interest towards the latest scientific theories of the day, as well as towards the network of ideas that served as their ground and context. The greatest Psychological Schools – Psychoanalysis, the Gestalt theory, Phenomenology, among others – soon appeared in Spain, and by the beginning of the 20th century Spanish scientific psychology was formed. In the institutionalization of this new science, the Spanish philosopher, José Ortega y Gasset, took a leading part. Already as a young man Ortega showed great interest in psychology and as a mature philosopher he even dedicated an entire university course to the question of Psychology with the title “System of Psychology”, in 1915-16. These lectures -which embedded various central psychological issues in philosophical discourse – are of great interest even today.